2003
DOI: 10.1046/j.1365-2362.2003.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bosentan on neointimal response following coronary angioplasty

Abstract: Oral treatment with bosentan reduces neointimal development following coronary angioplasty in this experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These studies indicate that activation of the ET-1/ET receptor system is involved in the development of vascular remodeling after vascular injury. Actually, a selective ET A receptor and ET A /ET B dual receptor antagonist show vasoprotective effects via inhibition of neointimal formation after balloon injury [9, 1315]. In a clinical study, it was reported that ET-1 levels in the coronary circulation were increased after percutaneous transluminal coronary angioplasty (PTCA) [16].…”
Section: Vascular Et-1/et Receptor System In a Pathological Statementioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that activation of the ET-1/ET receptor system is involved in the development of vascular remodeling after vascular injury. Actually, a selective ET A receptor and ET A /ET B dual receptor antagonist show vasoprotective effects via inhibition of neointimal formation after balloon injury [9, 1315]. In a clinical study, it was reported that ET-1 levels in the coronary circulation were increased after percutaneous transluminal coronary angioplasty (PTCA) [16].…”
Section: Vascular Et-1/et Receptor System In a Pathological Statementioning
confidence: 99%
“…In other words, antagonism of the ET A receptor is essential for the inhibition of neointimal formation after balloon injury, irrespective of the presence of ET B receptor-mediated actions. This hypothesis could explain why both selective ET A receptor and nonselective ET A /ET B dual receptor antagonists are equally effective in suppressing neointimal formation [9, 1315]. …”
Section: Pathophysiological Roles Of the Etb Receptor In Vascular mentioning
confidence: 99%
“…ET B upregulation in SMC, mediating vasoconstriction and proliferation in cardiovascular disease,18,19 might explain studies reporting similar benefit from mixed ET A/B and selective ET A antagonism in reducing lesion formation23,39,40 (despite the protective roles of ET B in several tissues; e.g. EC, kidney).…”
Section: Discussionmentioning
confidence: 99%
“…An endothelin A/B receptor antagonist contributed to reduction of intimal hyperplasia in an organ culture of human saphenous veins and prevented neointimal development of coronary angioplasty in pigs, which is in accordance with our experiment. 23 , 24 αSMA is the specific protein of vascular smooth muscle cells and the expression of αSMA can reflect the hyperplasia of vascular smooth muscle cells. In our experiment, we examined the values of αSMA in grafted veins with RT-PCR and found that the values in the α-CA, RPM, and α-CA-RPM groups was lower than in the control group.…”
Section: Discussionmentioning
confidence: 99%